Multicommunicating and The Future of Work - Stephens, Keri K.; Harris, Anastazja G.; Waters, Eric D. (2020)
ABSTRACT Multicommunicating, the practice of using technology to carry on multiple near-simultaneous conversations, has been studied for almost two decades, but much of the research has focused on in-person meetings. This practice has new meaning in light of the COVID-19 Pandemic as more people are working remotely—many new to this practice—and teams are looking for ways to be more productive. This position statement paper establishes why multicommunicating is an important concept for the growing prevalence of remote work and the future of work. In addition to reviewing the relevant research, this paper answers some key questions around this practice including sites of multicommunicating, why people engage in this practice, and typical outcomes. We conclude by describing current implications that invite research to further understand how this practice could and should be studied, now and in the future. Keywords multicommunicating, virtual teams, remote work, multitasking, attention, work, meetings ABOUT THE AUTHORS Keri K. Stephens The University of Texas at Austin keristephens@austin.utexas.edu Keri K. Stephens, PhD, is an Associate Professor in Organizational Communication Technology in the Moody College of Communication at The University of Texas at Austin. Her research program examines the role of technology in organizational practices. She has authored over 80 articles, and her two most recent books are New Media in Times of Crisis (2019, Routledge), and Negotiating Control: Organizations and Mobile Communication. https://commstudies.utexas.edu/faculty/keri-stephens Anastazja G. Harris The University of Texas at Austin harrisana@utexas.edu Eric D. Waters Marquette University eric.waters@marquette.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).